Number of deaths among HIV-infected adults in France in 2000, three-source capture–recapture estimation - LEWDEN, C. (Cambridge University Press, 2006)
We estimated the number of deaths in France for the year 2000 in HIV-infected adults using three sources. The sources were (1) the ‘Mortalité 2000’ survey (M2000): 964 deaths were documented by 185 hospital wards involved in HIV management; (2) 1288 death certificates with a mention of HIV infection (INSERM-CepiDc) and (3) the French hospital database on HIV infection (FHDH) identified 654 deaths. The capture–recapture method was used with log-linear modelling. Overall 1559 deaths were observed. Estimation of the number of deaths in France was 1699 (95% CI 1671–1727). The completeness of M2000, CepiDc and FHDH were 55%, 76% and 38% respectively. Diversification of diseases and of causes of death in HIV-infected adults may explain: (1) the diversification of physicians involved in their management and incomplete coverage of M2000 and FHDH, and (2) why HIV infection was not mentioned in all death certificates.